The Wedding Music Industry: An Adaptation of Andy Irawan Music during the Covid-19 Pandemic - Natalia, Violinna Wynsa; Wadiyo, Wadiyo; Utomo, Udi (Universitas Negeri Semarang, 2020)
This study aims to identify, reveal, analyze and describe adaptation of Andy Irawan Music's efforts to deal with the Covid-19 pandemic in the wedding music industry. The author uses an interdisciplinary approach, by borrowing theories and concepts from the disciplines of musicology, sociology, and economics. The object in this study is industry and adaptation, with the subject Andy Irawan Music. The research design uses an interpretive case study located in Semarang. The data were collected through observation, interviews, and documentation. The results show that Andy Irawan Music could adapt during the Covid-19 pandemic. Adaptation efforts made by Andy Irawan Music include appearing with new formations, optimizing the use of social media/ digital platforms, applying virtual music, following recommended health protocols, participating in wedding showcases, and creating Andy Irawan Disciples.